A Critique on the Book Everyday Life of the Urban Precariat - Baharak Mahmoodi; Abbas Varij Kazemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article has been written with the aim of critical study on the book Everyday Life of Urban Precariat (2013-2011) written by Alireza Sadeghi.  This book is considered as a collection of works written in the theoretical-methodological tradition of Bayat and according to the author, it is readable in the continuation of Bayat's book "Street Policies" which was written in 1997. The results of this critical study show that although the information and evidence presented in the book, which has been analyzed in an ethnographic manner, indicate the depth and breadth of this research, the fact is that the book is one of its original examples of "street politics". He has not stepped beyond. Also, showing the negligence and insignificance of the role of the poor in reproducing the inferiority situation and urban irregularities is a point that can be seen in the design and summary of the present book.